Studi Kualitatif Faktor yang Mempengaruhi Pemberian MP-ASI di Posyandu Melati 1 Kota Malang - Hiya Alfi Rahmah; Catur Saptaning Wilujeng (Journal of Bionursing, 2020)
Background. When children reach the age of more than 6 months, obtaining adequate nutrition is not enough from breastfeeding alone. Completion of a balanced diet in the presence of complementary food may be achieved. It is important for a mother to fulfill adequate complementary feeding practices. This study aimed to analyze factors influencing the complementary feeding practices of mothers with children aged 6-12 months.Methods. This was a qualitative study where the design was an exploratory case study. The number of informants was 6 mothers of children aged 6-12 months. Data were collected by in-depth interviews and observations.Results. The important things to be discussed about complementary feeding practices were types and methods of cooking. Factors influencing complementary feeding practices of mothers with children aged 6-12 months were capability which includes knowledge about adequate complementary feeding practices, opportunity to get information and social support, and also motivation which defined as thought or efforts to provide adequate complementary feeding. Conclusion. Factors influencing complementary feeding practices of mothers with children aged 6-12 months were capability, opportunity and motivation.